2020
DOI: 10.1101/2020.11.22.393298
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GEMC1-MCIDAS transcriptional program regulates multiciliogenesis in the choroid plexus and acts as a barrier to tumorigenesis

Abstract: Multiciliated cells (MCCs) in the brain include the ependymal cells and choroid plexus (CP) epithelial cells. The CP secretes cerebrospinal fluid that circulates within the ventricular system, driven by ependymal cilia movement. However, the mechanisms and functional significance of multiciliogenesis in the CP remain unknown. Deregulated oncogenic signals cause CP carcinoma (CPC), a rare but aggressive pediatric brain cancer. Here we show that aberrant NOTCH and Sonic Hedgehog signaling in mice drive tumors th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…This contrasts with mouse ependymal cells where loss of Gmnc/Gemc1 completely abolishes ciliogenesis, and prevents the maturation of ependymal cells [57,58] and MCCs of the ChP [80]. Thus, ciliary defects in the gmnc mutant zebrafish brain resembles more closely the phenotype of Mcidas knockout mice, where multiciliated precursor cells are still specified, but do not acquire multiciliation and instead generate a single motilelike cilium [55,80]. These results are also similar to our earlier report of gmnc loss-of-function in the zebrafish embryonic kidneys where MCC precursors differentiate with single motile cilia [59].…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…This contrasts with mouse ependymal cells where loss of Gmnc/Gemc1 completely abolishes ciliogenesis, and prevents the maturation of ependymal cells [57,58] and MCCs of the ChP [80]. Thus, ciliary defects in the gmnc mutant zebrafish brain resembles more closely the phenotype of Mcidas knockout mice, where multiciliated precursor cells are still specified, but do not acquire multiciliation and instead generate a single motilelike cilium [55,80]. These results are also similar to our earlier report of gmnc loss-of-function in the zebrafish embryonic kidneys where MCC precursors differentiate with single motile cilia [59].…”
Section: Discussionmentioning
confidence: 81%
“…Upon loss of the central regulator of multiciliation, gmnc, we found that zebrafish ependymal MCCs differentiate a single cilium, implying that Gmnc activity does not impact motile ciliogenesis per se but only the process of multiciliation. This contrasts with mouse ependymal cells where loss of Gmnc/Gemc1 completely abolishes ciliogenesis, and prevents the maturation of ependymal cells [57,58] and MCCs of the ChP [80]. Thus, ciliary defects in the gmnc mutant zebrafish brain resembles more closely the phenotype of Mcidas knockout mice, where multiciliated precursor cells are still specified, but do not acquire multiciliation and instead generate a single motilelike cilium [55,80].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…ciliogenesis, per se, but only the process of multiciliation. This contrasts with mouse ependymal cells, where loss of Gmnc/ Gemc1 completely abolishes ciliogenesis and prevents the maturation of ependymal cells (Kyrousi et al, 2015;Terré et al, 2016) and MCCs of the ChP (Li et al, 2020). Thus, ciliary defects in the gmnc mutant zebrafish brain resembles more closely the phenotype of Mcidas knockout mice, where multiciliated precursor cells are still specified but generate a single motile-like cilium (Lu et al, 2019;Li et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…This raises the question as to why foxj1a is needed later in development in this population of cells. It is possible that foxj1a is expressed because Gmnc eventually induces the expression of both Foxj1 orthologs ( Zhou et al., 2015 ; Stubbs et al., 2012 ; Chong et al., 2018 ; Terré et al., 2016 ; Arbi et al., 2016 ; Kyrousi et al., 2015 ; Li et al., 2020 ) without discriminating between them. Alternatively, MCCs could require both foxj1 genes to transcribe enough motile cilia-specific gene transcripts for multiciliation.…”
Section: Discussionmentioning
confidence: 99%